Impact of the social context on the prognosis of Chagas disease patients: Multilevel analysis of a Brazilian cohort. - Ariela Mota Ferreira; Éster Cerdeira Sabino; Lea Campos de Oliveira; Cláudia Di Lorenzo Oliveira; Clareci Silva Cardoso; Antônio Luiz Pinho Ribeiro; Renata Fiúza Damasceno; Maria do Carmo Pereira Nunes; Desirée Sant' Ana Haikal (Public Library of Science (PLoS), 2020)
The present study aims to investigate how the social context contributes to the prognosis of Chagas disease (CD). This is a multilevel study that considered individual and contextual data. Individual data came from a Brazilian cohort study that followed 1,637 patients who lived in 21 municipalities to which CD is endemic, over two years. Contextual data were collected from official Brazilian government databases. The dependent variable was the occurrence of cardiovascular events in CD during the two-year follow-up, defined from the grouping of three possible combined events: death, development of atrial fibrillation, or pacemaker implantation. Analysis was performed using multilevel binary logistic regression. Among the individuals evaluated, 205 (12.5%) manifested cardiovascular events in CD during two years of follow-up. Individuals living in municipalities with a larger rural population had protection for these events (OR = 0.5; 95% CI = 0.4-0.7), while those residing in municipalities with fewer physicians per thousand inhabitants (OR = 1.6; 95% CI = 1.2-2.5) and those living in municipalities with lower Primary Health Care (PHC) coverage (OR = 1.4; 95% CI = 1.1-2.1) had higher chances of experiencing cardiovascular events. Among the individual variables, the probability of experiencing cardiovascular events was higher for individuals aged over 60 years (OR = 1.4; 95% CI = 1.01-2.2), with no stable relationship (OR = 1.4; 95% CI = 0.98-2.1), without previous treatment with Benznidazole (OR = 1.5; 95% CI = 0.98-2.9), with functional class limitation (OR = 2.0; 95% CI = 1.4-2.9), with a QRS complex duration longer than 120 ms (OR = 1.5; 95% CI = 1.1-2.3), and in individuals with high NT-proBNP levels (OR = 6.4; 95% CI = 4.3-9.6). CONCLUSION: The present study showed that the occurrence of cardiovascular events in individuals with CD is determined by individual conditions that express the severity of cardiovascular involvement. However, these individual characteristics are not isolated protagonists of this outcome, and the context in which individuals live, are also determining factors for a worse clinical prognosis.